Optimization of resources by drug management: A multicentred web-administered study on the use of ipilimumab in Italy. (June 2019) - Damuzzo, V; Russi, A; Chiumente, M; Masini, C; Rebesco, B; Gregis, F; Nozza, S; Pigozzo, J; Chiarion-Sileni, V; Palozzo, AC
Objective: In a scenario of new expensive cancer therapies entering the market, strategies of optimisation and cost containment are crucial in oncology care. Better management of drug waste and centralization of drug preparation can be effective strategies to achieve these goals. The aim of this work is to describe the economic management of a high cost anticancer drug (ipilimumab) in some Italian reference centres. Methods: This was an observational, multicentred study in which economical and clinical data of 21 cancer centres (418 patients) were collected during the enrollment period from February 2013 to August 2014. The follow-up period ended in July 2015. Results: Participants purchased 10.7% more vials of ipilimumab than necessary for compounding. The results were variable among centres, and only five centres had a deviation lower than 5% between the drug purchased and the drug prescribed. Hospitals applying the drug day reached a statistically significant residual of drug effectively used compared to the amount prescribed (P = 0.018). Consequently, the price for treating a model patient was significantly lower in those hospitals (median spare of 7456 euro per patient). Conclusions: This study demonstrated that the careful management of drug waste and the application of drug-day, through a proper selection of vial and the ability to use the leftover drug, can generate economic savings. However, tailoring the drug stock to clinical need is still an open issue which deserves further analysis.